Sodium butyrate-induced death-associated protein kinase expression promote Raji cell morphological change and apoptosis by reducing FAK protein levels - Zhang Hai-tao; Feng Zhe-ling; Wu Jun; Wang Ya-jun; Guo Xia; Liang Nian-ci; Zhu Zhen-yu; Ma Jian-quan (Acta Pharmacologica Sinica; Vol 28, No 11 (November 2007): Acta Pharmacologica Sinica, 2016)
Aim: To investigate the role of death-associated protein kinase (DAPK) on the apoptosis of Raji cells induced by sodium butyrate. Methods: The apoptosis of Raji cells were induced by sodium butyrate for 2, 4, 6, 8, and 10 d. Simultaneity, the Raji cells were inhibited to adhere on culture flask by polyHEME. Cell viability was detected by 3-(4, 5-dimethylthiazol-2-yl)-2, 5-diphenyltetrazolium bromide method and the cell apoptosis percentage was estimated by flow cytometry. DAPK and focal adhesion kinase (FAK) expression were measured by Western blotting. Coding sequence on the C-terminal of DAPK, which can suppress the function of DAPK, was tranfected into the Raji cells to investigate whether the C-terminal of DAPK could inhibit the apoptosis of Raji cells induced by sodium butyrate. Results: After being treated with sodium butyrate, the Raji cells expressed DAPK and displayed many protrusions to adhere onto the culture flask. The Raji cells were susceptive to apoptosis when they were inhibited adhesion by polyHEME. At that time, the cell viability decreased, the cell apoptosis percentage increased and the protein levels of total FAK were reduced. The Raji cells, which were transfected with the coding region on the C-terminal of DAPK, sustained apoptosis and the FAK protein level when treated with sodium butyrate. Conclusion: Sodium butyrate induced DAPK expression. It caused the Raji cells to display many protrusions all around the cells and adhere onto the culture flask. DAPK expression prompted apoptosis by reducing the FAK protein level in sodium butyrate-induced Raji cells.